2010
DOI: 10.1136/oem.2010.057448
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor work and risk for Parkinson's disease: a population-based case–control study

Abstract: Objectives Sunlight is the main contributor to vitamin D in humans. Since inadequate levels of vitamin D have been linked to increased risks for neurodegenerative diseases, we examined whether outdoor work is associated with a reduced risk for Parkinson’s disease in a population-based case–control study of Danish men. Methods We identified 3819 men with a primary diagnosis of Parkinson’s disease in the period 1995–2006 in the Danish National Hospital Register and selected 19 282 age- and sex-matched populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 35 publications
3
32
0
1
Order By: Relevance
“…As for the outdoor activity, Kenborg et al (2011) recently reported that men working outdoors have a lower risk of PD, which is in line with our results. The mechanism of this finding was still unclear.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…As for the outdoor activity, Kenborg et al (2011) recently reported that men working outdoors have a lower risk of PD, which is in line with our results. The mechanism of this finding was still unclear.…”
Section: Resultssupporting
confidence: 93%
“…Outdoor activities were also reported to be linked to PD (Kenborg et al, 2011). Additionally, the dynamic changes of serum vitamin D are determined by dietary and sun avoidance factors, as 20% vitamin D is obtained from food (eggs, fish, animal liver, and dairy products), while 80% is from skin synthesis as a product of skin 7-dehydrocholesterol transformations induced by ultraviolet radiation (American Diabetes Association, 2007;Marcinowska-Suchowierska et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the strongest evidence is from a study of outdoor work and risk of Parkinson's disease in Denmark. The odds ratio decreased consistently with respect to the amount of outdoor work, reaching a low of 0.72 (95% confidence interval 0.63-0.82) for maximal outdoor work (Kenborg et al, 2011).…”
Section: Parkinson's Diseasementioning
confidence: 96%
“…Acknowledging that the diagnosis of MSA is challenging and that MSA patients frequently are misdiagnosed as suffering from IPD (ICD-10, G20.9), the author group initiated cooperation with the Danish Parkinson's Disease in Denmark (PASIDA) study [13] . Of the 45 potential MSA patients in the PASIDA cohort, 15 patients fulfilled the diagnostic criteria for probable MSA and were included.…”
Section: Patient Identificationmentioning
confidence: 99%
“…), we expanded our diagnostic definition to include G23.8 and G28.9. In addition, we incorporated 15 probable MSA patients from the ongoing PASIDA study of Parkinson's disease in Denmark [13,26] . We may have missed MSA-C patients who were classified under codes for ataxia-associated disease.…”
Section: Strengths and Limitationsmentioning
confidence: 99%